Efeitos de um programa de psicomotricidade no bem-estar e na marcha em idosos - Santos, Sarah Lins (2013)
Introduction: Because of aging, the human undertakes some physiological structures important for gait performance is noteworthy that the changes of gait in the elderly are processed in relation to factors both physiological and emotional, interfering with the lifestyle that the elderly presents. Objective: to investigate the effect of a program of psychomotor activities in gait and physical well-being, mental and social of elderly,. Methodology: It is an intervention study, without group control, descriptive, with quantitative-qualitative approach, conducted in a Clinical School of the Federal University of Paraíba, João performance of gait (POMA-BRAZIL). These evaluations were part of the triage of participants, being PEEM and POMA, Pessoa-PB. The population of the study was composed by 15 elderly. For data collection was utilized an instrument with socio demographic data, clinical data and physical examination, the mini mental state examination and the evaluation of functional performed in three moments of the research, every two months. The study was conducted in the period from August to December 2011. Referring to ethical considerations, the study was in accordance to the rules of Resolution1196/96. Regarding the intervention procedure were carried out psychomotor activities whose purpose a muscle strengthening from the psychomotor elements, favoring a better gait performance, being developed in the water and soil. After finishing the psychomotor program were identified perceptions of elderly through the individual interview technique of which guiding question was: What is the perception about the effects of the psychomotor program in your life? Their statements were recorded, which contributed so that the speeches could be transcribed with higher accuracy and reliability. For quantitative data analysis was utilized descriptive statistics and Friedman s test, from the qualitative point of view, the content analysis of Bardin. Results and data analysis: There was a significant difference between the evaluations of gait performance (Χ2FR= 17,7; gl= 2; p=0,0001), mainly between the second and the third evaluation (p<0,05). In synthesis, satisfactory results were found for the following variables: step length, step width, step height, the step symmetry, trunk stability, turning during walking, running and support for the midline deviation, which can be assigned practical effects of psychomotor. Final Considerations: Become is an indispensable for the promotion for the Health of the elderly, because the activities will provide an improved quality of life and the correction of gait in the elderly.